2017
DOI: 10.1101/111567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PGC-1α coordinates with Bcl-2 to control cell cycle in U251 cells through reducing ROS

Abstract: B-cell lymphoma 2 (Bcl-2) has a dual function, acting both as an oncogene 20 and an anti-tumor gene. It is well known that Bcl-2 exerts its tumor promoting 21 function through the mitochondrial pathway. However, the mechanism by which

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…They demonstrated that glycolysis-induced lactic acidosis, but not glycolysis-related lactosis or acidosis, enhances the expression of Bcl-2 and phosphorylation of Akt, and suppresses the function of the mammalian target of rapamycin (mTOR), thereby enabling the cancer cells to survive under unfavorable and stringent growth conditions (Wu et al, 2012). Since glycolysis-induced lactic acidosis is widely accepted as an intrinsic factor that can induce chemoresistance in a variety of malignancies (Ganapathy-Kanniappan and Geschwind, 2013;Suh et al, 2014;Icard et al, 2018;Yao K et al, 2018), in this study, we hypothesized that BM-MSCs, particularly their derived microRNAs, could influence intracellular glycolysis and enhance the chemoresistance of ovarian cancer. Based on supportive data obtained from our in vitro cancer cell models, we investigated the exact microRNA molecule(s) released by BM-MSCs that induced the glycolysisrelated chemoresistance in ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that glycolysis-induced lactic acidosis, but not glycolysis-related lactosis or acidosis, enhances the expression of Bcl-2 and phosphorylation of Akt, and suppresses the function of the mammalian target of rapamycin (mTOR), thereby enabling the cancer cells to survive under unfavorable and stringent growth conditions (Wu et al, 2012). Since glycolysis-induced lactic acidosis is widely accepted as an intrinsic factor that can induce chemoresistance in a variety of malignancies (Ganapathy-Kanniappan and Geschwind, 2013;Suh et al, 2014;Icard et al, 2018;Yao K et al, 2018), in this study, we hypothesized that BM-MSCs, particularly their derived microRNAs, could influence intracellular glycolysis and enhance the chemoresistance of ovarian cancer. Based on supportive data obtained from our in vitro cancer cell models, we investigated the exact microRNA molecule(s) released by BM-MSCs that induced the glycolysisrelated chemoresistance in ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 99%